Being in the World : Dialogue and Cosmopolis - Dallmayr, Fred R. (Fred Reinhard), 1928- (Book collections on Project MUSE., 2013)
It is commonly agreed that this is the era of globalization, but the profound consequences of this development are rarely understood. Usually, globalization is equated with the expansion of economic and financial markets and the proliferation of global networks of communication. In truth, much more is at stake: traditional concepts of individual and national identity, as well as perceived relationships between the self and others, are undergoing profound change. Every town has become a potential cosmopolis - an international city - affecting the way that people conceptualize the relationship between public order and political practice. In this book, a political theorist explores the globe's transition from the traditional Westphalian system of states to an interlocking cosmopolitan network.